The challenges of access to Water Supply and Sanitary Sewage services in Northern Brazil, in times of Covid-19 pandemic (Research, Society and Development, 2021)
The Challenges of Accessing Water Supply and Sanitation Services in Times of Covid-19 Pandemic. The research was divided into 5 steps. Initially, bibliographic data survey was carried out. Then, the sanitation indicators worked on in the research were defined. In step III, the virtual form for data collection was created. Finally, the obtained data were discussed and analyzed. As a result of this research, it was found that not all CDA residents had access to basic water supply and sanitation services. Furthermore, in 13.5% of households there was a lack of water at least once a week. Also, 73.7% of homes did not have access to a sewage collection network. And 24.4% used a black cesspool to dispose of the generated sewage. In this scenario, the importance of planning and investing in basic sanitation structures is renewed both in the capitals and in the municipalities in the interior of the State of Pará. Because, it is understood that this way it will be possible to reduce not only the contagion of COVID-19, but also of so many other diseases caused by the absence of basic sanitation services.